Polymorphisms in the Sortilin-Related Receptor 1 Gene Are Associated with Cognitive Impairment in Filipinos. (27th November 2014) - Casingal, Cristine R.; Daroy, Maria Luisa G.; Mapua, Cynthia A.; Florendo, Dianne Jane A.; Natividad, Filipinas F.; Dominguez, Jacqueline C.
Abstract : Background/Aims . Sortilin-related receptor 1 (SORL1) is involved in the neuronal transport processes and plays a role in the formation of amyloid plaques. This study investigated the association of 6 SORL1 single nucleotide polymorphisms (SNPs 8, 9, 10, 13, 19, and 23) with cognitive impairment (CI) in Filipinos. Methods . DNA samples from 484 subjects (100 Alzheimer's Disease (AD) cases, 109 mild cognitive impairment (MCI) cases, 18 other types of CI, and 257 no dementia controls (NDC)) were genotyped using TaqMan SNP Genotyping Assays. Data Analysis . Our study showed strong linkage disequilibrium in the SNPs 8, 9, and 10 block. Our results showed that CI was significantly associated with SNPs 13 and 23. None of the SORL1 SNPs studied was associated with AD while SNPs 8, 9, 10, and 23 were associated with MCI. Conclusion . The findings had provided evidence that SORL1 may predispose individuals to CI. Further studies are needed to clarify the role of SORL1 in Filipinos with AD.